Propuesta de una campaña de comunicación y relaciones públicas para dar a conocer e involucrar a la ciudadanía Esmeraldeña en el éxito del proyecto “Intervención Urbana Las Palmas” liderado por el ilustre Municipio de Esmeraldas, en la ciudad de Esmeraldas - Romero Mora, María Gabriela (2013)
The present research work was to conduct a communication plan for the Illustrious Municipality of the city of Esmeraldas, in order to make known to the public esmeraldeña the urban regeneration project and tourism called “Urban Intervention Las Palmas” through communication tools that are designed to inform and involve the Esmeraldas and tourists in general. For the implementation of this thesis was the following chapters: The first chapter contains information on the historical background, culture, attractions Esmeraldas, as is the beach located within the city called “Las Palmas” which will develop the project mentioned above also refers to the history, institutional philosophy, projects the Municipality of Esmeraldas, Project lead institution. The second chapter refers to communication, the importance of maintaining an efficient and effective communication between the public linked in an organization. The third chapter presents all about public relations, the tools used and how campaigns are planned and implemented through action programs to achieve dissemination and public acceptance. In the fourth chapter presents field research, and considers research techniques for the development of the thesis, it was necessary to analyze the perception of the public, using surveys, whose aim was to investigate the knowledge of the citizens of the city of Esmeraldas on the Project; equally relevant celebrity interviews in which the Project is developed. In the fifth chapter presents the general and specific objectives, strategies, actions, schedule, budget and all communications related to the plan. It ends with the conclusions and recommendations that are part of the proposal.